2011
DOI: 10.1038/tp.2011.61
|View full text |Cite
|
Sign up to set email alerts
|

Disease- and age-related changes in histone acetylation at gene promoters in psychiatric disorders

Abstract: Increasing evidence suggests that epigenetic factors have critical roles in gene regulation in neuropsychiatric disorders and in aging, both of which are typically associated with a wide range of gene expression abnormalities. Here, we have used chromatin immunoprecipitation-qPCR to measure levels of acetylated histone H3 at lysines 9/14 (ac-H3K9K14), two epigenetic marks associated with transcriptionally active chromatin, at the promoter regions of eight schizophrenia-related genes in n=82 postmortem prefront… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(71 citation statements)
references
References 70 publications
2
68
0
1
Order By: Relevance
“…For example, the GAD1(GAD67) GABA synthesis enzyme gene promoter shows in the SCZ cortex a shift from facilitative histone acetylation and H3K4 methylation toward repressive histone methylation markings [68,69]. Interestingly, such histone PTM changes have been reported in animals exposed to suboptimal postnatal care and parenting [70] or antimitotic drugs during prenatal development [71], which would be consistent with the neurodevelopmental hypothesis of schizophrenia.…”
Section: Histone Modificationssupporting
confidence: 66%
“…For example, the GAD1(GAD67) GABA synthesis enzyme gene promoter shows in the SCZ cortex a shift from facilitative histone acetylation and H3K4 methylation toward repressive histone methylation markings [68,69]. Interestingly, such histone PTM changes have been reported in animals exposed to suboptimal postnatal care and parenting [70] or antimitotic drugs during prenatal development [71], which would be consistent with the neurodevelopmental hypothesis of schizophrenia.…”
Section: Histone Modificationssupporting
confidence: 66%
“…HDAC inhibitors have been used to increase acetylated levels of genes, thus restoring the expression of genes that are compromised during aging (Peleg et al, 2010;Tang et al, 2011). In addition, preclinical and clinical studies have found that VPA, a class I HDAC inhibitor, can augment the therapeutic effects of antipsychotics (Guidotti et al, 2009;Suzuki et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The GAD67 transcript is downregulated in cerebral and cerebellar cortex of a significant portion of subjects diagnosed with schizophrenia, depression or autism and this type of alteration may contribute to desynchronization of cortical networks and cognitive dysfunction because of defective GABAergic inhibition Benes et al, 2007;Blatt and Fatemi, 2011;Curley and Lewis, 2012;Guidotti et al, 2000;Volman et al, 2011). Importantly, both in human and rodent cerebral cortex, Gad1/GAD1 promoter-associated DNA methylation, and multiple histone acetylation and methylation markings are highly regulated during the course of normal development and aging (Huang and Akbarian, 2007a;Huang et al, 2007b;Siegmund et al, 2007;Tang et al, 2011;Zhang et al, 2010b), and are sensitive to exposure of histone deacetylase inhibitor drugs and even to the atypical antipsychotic, clozapine (Chen et al, 2011;Huang et al, 2007b). These findings, taken together, would imply that epigenetic decoration and activity of the Gad1/ GAD1 promoter in the prefrontal cortex is highly sensitive to the impact of multiple non-genetic factors such as drug exposure, disturbed neurodevelopment and so on.…”
Section: Epigenetics and Transcriptional (Dys) Regulation In Diseasedmentioning
confidence: 99%
“…Still, hundreds of promoters are subject to epigenetic changes that seemingly continue into old age, and these data, taken together, leave little doubt that chromatin structures undergo remodeling throughout the lifespan of the human brain (Hernandez et al, 2011;Numata et al, 2012;Siegmund et al, 2007), including neurons and other terminally differentiated cells (Cheung et al, 2010). Based on postmortem brain work, epigenetic risk architectures are beginning to emerge for a number of common psychiatric conditions and disorders, including autism (Shulha et al, 2011), schizophrenia (Akbarian, 2010), depression and bipolar disorder (Gamazon et al, 2012;Tang et al, 2011) and alcoholism (Taqi et al, 2011) Table 1). We predict that only very few, if any, loci will show group-based differences when assayed in genome-wide epigenetic screens.…”
Section: Synopsis and Outlookmentioning
confidence: 99%